Bobot dan Panjang Relatif Organ Limfoid Itik Magelang Jantan yang Mendapatkan Penambahan Ekstrak Kulit Jengkol dan Bacillus amyloliquifaciens dalam Air Minum - Pradipta Bayuaji Pramono; Mikael Sihite (Journal of Livestock Science and Production, 2023)
This study aimed to determine the relative weight and length of the lymphoid organs of male Magelang ducks that received phytobiotics from jengkol peel extract and probiotics based on Bacillus amyloliquefaciens. The materials used in this study were 100 male Magelang ducks, jengkol skin extract, Bacillus amyloliquefaciens isolates, and commercial duck feed. The experimental design was completely randomized (CRD) with five treatments and four replications. The treatment applied was the difference in the percentage of jengkol peel extract + Bacillus amyloliquefaciens at a dose of P0: (without additional treatment); P1 (0.05% + 0.5%); P2 (0.1% + 1%); P3 (0.15% + 1.5%); and P4(0.2% +2%) in drinking water. Data were analyzed using analysis of variance  (ANOVA) at the 5% level. Significantly different data were further tested using Duncan's Multiple Range Test (DMRT). The variables observed included the relative weight and length of thymus, bursa of Fabricius, and spleen. The results showed that the addition of jengkol peel extract and Bacillus amyloliquefaciens at different doses did not affect the relative length and weight of thymus, bursa Fabricius, and spleen of male Magelang ducks.